SMART CONTRACTS IN DECENTRALIZED ENERGY MARKETS: OPPORTUNITIES AND REGULATORY CHALLENGES - Romanuke, V. V. (Systems and Technologies, 2026)
The accelerating digitalization of the energy sector is redefining how electricity is generated, traded, and consumed. Among emerging innovations, smart contracts being self-executing programs embedded on blockchains have become pivotal to the development of decentralized energy markets. This article reviews the state of knowledge and practical progress in applying smart contracts to energy systems, with particular attention to their potential in Ukraine’s evolving energy and digital infrastructure. Through a systematic analysis of academic studies, pilot projects, and policy frameworks, the article identifies the main opportunities, challenges, and future trajectories of blockchain-based automation in energy markets. The starting sections introduce the conceptual foundations of smart contracts, highlighting their essential properties of transparency, immutability, and autonomy. These characteristics enable direct peer-to-peer transactions without intermediaries, potentially lowering transaction costs and improving market efficiency. The subsequent analysis focuses on how smart contracts can support decentralized energy trading, renewable integration, and dynamic pricing, using examples from Australia’s Power Ledger, Brooklyn Microgrid in the United States, and Europe’s Enerchain, WePower, and Sunchain initiatives. To complement international evidence, the article discusses Ukraine’s readiness for pilot adoption in microgrid environments, given its digital transformation agenda and renewable energy policies. The study further examines technological, regulatory, and security challenges hindering large- scale deployment. Issues such as interoperability, scalability of consensus algorithms, and the legal enforceability of smart contracts remain critical barriers. Nevertheless, emerging frameworks like regulatory sandboxes and advances in IoT and AI integration offer pathways to overcome them. MATLAB-based simulation examples illustrate the potential for dynamic pricing and automated market balancing. The article concludes with strategic recommendations for policymakers, engineers, and researchers by emphasizing the need for hybrid architectures combining blockchain, artificial intelligence, and energy optimization models. Overall, the article underscores that while smart contracts promise to democratize and decarbonize energy systems, their success ultimately depends on coordinated technical innovation and adaptive governance.